Self-healing tannic acid-based polyurethane as well as preparation method and application thereof

By using tannin as a crosslinking agent in polyurethane materials, self-healing tannin-based polyurethanes are prepared, which solves the problems of high and low self-repair temperature and low efficiency of existing polyurethane materials, achieves self-repair effect at high efficiency and low temperatures, and improves the thermal stability and biodegradation performance of the material.

CN119569985APending Publication Date: 2025-03-07ZHEJIANG YUANRONG TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411730993.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing polyurethane materials have high self-repair temperature and low efficiency, making it difficult to meet the actual application needs.

Method used

Tannic acid is used as a crosslinking agent to prepare self-healing tannin-based polyurethane based on the prepolymer method, and combine castor oil, isophorone diisocyanate, bis(2-hydroxyethyl)disulfide and 1,4-butanediol and other materials to adjust the glass transition temperature and mechanical properties of the material.

Benefits of technology

A self-healing efficiency of 95% at lower temperatures (80°C) and shorter time (3h) is achieved, and the thermal stability and biodegradation performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569985A_ABST
    Figure CN119569985A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of self-repairing high polymer materials, and discloses self-healing tannic acid-based polyurethane as well as a preparation method and application thereof, tannic acid is taken as a cross-linking agent, castor oil is taken as polyol of polyurethane, isophorone diisocyanate is taken as polyisocyanate of polyurethane, bis (2-ethoxyl) disulfide and 1, 3-butanediol are taken as a crosslinking agent, and the self-healing tannic acid-based polyurethane is prepared by a one-step method. The preparation method comprises the following steps: by taking 1, 4-butanediol as a chain extender of polyurethane, preparing tannic acid-based polyurethane on the basis of a prepolymer method; the self-healing temperature of the tannic acid-based polyurethane film prepared from the tannic acid-based polyurethane is 80 DEG C, and the self-repairing efficiency is as high as 95%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of self-healing polymer materials, and in particular to a self-healing tannic acid-based polyurethane and a preparation method and application thereof. Background Art

[0002] The self-healing property of polymer materials refers to the ability of polymer materials to repair themselves under certain conditions after damage caused by external forces. "PORTA R, SABBAH M, DIPIERRO P. Bio-Based Materials for Packaging [J]. International Journal of Molecular Sciences, 2022." discloses a heat-driven intrinsic self-healing system based on a reversible phenol-carbamate bond; "GODINHO B, GAMA N, BARROS-TIMMONS A, et al. Recycling of different types of polyurethane foam wastes via acidolysis to produce polyurethane coatings [J]. Sustainable Materials and Technologies, 2021." confirms that the phenol-carbamate dynamic bond is stable at low temperatures, but dissociates and exchanges at high temperatures. However, the current self-healing temperature of polyurethane materials is relatively high (120°C) and the self-healing efficiency is relatively low (90%). Therefore, the inventors prepared a tannic acid-based polyurethane based on the prepolymer method, and studied the effects of the actual dosage changes of tannic acid and bis(2-hydroxyethyl) disulfide on the glass transition temperature Tg, mechanical properties and self-healing properties of polyurethane. At the same time, lipase was used to evaluate the biodegradability of tannic acid-based polyurethane films. Summary of the invention

[0003] In view of the shortcomings of the prior art, the object of the present invention is to provide a self-healing tannic acid-based polyurethane and a preparation method and application thereof.

[0004] In order to achieve the first purpose, the present invention provides the following technical solutions:

[0005] A self-healing tannic acid-based polyurethane film is prepared based on a prepolymer method using tannic acid as a crosslinking agent, castor oil as a polyol of the polyurethane, isophorone diisocyanate as a polyisocyanate of the polyurethane, bis(2-hydroxyethyl) disulfide and 1,4-butanediol as chain extenders of the polyurethane.

[0006] Preferably, when preparing the tannic acid-based polyurethane, the solvents are butanone and N,N-dimethylformamide, and the butanone and N,N-dimethylformamide are dehydrated using activated 4a type molecular sieves for a dehydration time of one week.

[0007] Preferably, the castor oil is vacuum dried at 120° C. for 2 h; and the 1,4-butanediol and tannic acid are vacuum dried at 60° C. for 3 h before use.

[0008] In order to achieve the second purpose, the present invention provides the following technical solutions:

[0009] A method for preparing a self-healing tannic acid-based polyurethane comprises the following steps:

[0010] Accurately weighed castor oil and bis(2-hydroxyethyl) disulfide are added to a round-bottom flask under a nitrogen atmosphere, the mixture is heated under continuous stirring, isophorone diisocyanate is slowly added, and then a catalyst and butanone are added to react to obtain a prepolymer; keeping the heating temperature unchanged, tannic acid and 1,4-butanediol dissolved in N,N-dimethylformamide are added to further react to obtain a tannic acid-based polyurethane.

[0011] Preferably, the heating temperature is 70°C.

[0012] Preferably, the catalyst is dibutyltin dilaurate.

[0013] In order to achieve the third purpose, the present invention provides the following technical solutions:

[0014] The invention discloses an application of a self-healing tannic acid-based polyurethane for preparing a tannic acid-based polyurethane film.

[0015] The preparation method of the tannic acid-based polyurethane film is as follows: the prepared tannic acid-based polyurethane is transferred to a dry and clean polytetrafluoroethylene film mold, and cured at room temperature; then the film is transferred to a blast oven for drying, the film is carefully removed, and stored in a desiccator for later use.

[0016] Preferably, the curing time is 48 hours.

[0017] Preferably, the temperature in the blast oven is 60° C. and the drying time is 48 hours.

[0018] The present invention has significant technical effects due to the adoption of the above technical solution:

[0019] The present invention uses tannic acid as a crosslinking agent, castor oil as a polyol of polyurethane, isophorone diisocyanate as a polyisocyanate of polyurethane, bis(2-hydroxyethyl) disulfide and 1,4-butanediol as chain extenders of polyurethane, and prepares a tannic acid-based polyurethane based on a prepolymer method. The glass transition temperature (Tg) of the tannic acid-based polyurethane film gradually increases with the increase of the amount of tannic acid, while the glass transition temperature (Tg) of the tannic acid-based polyurethane remains unchanged with the increase of the amount of bis(2-hydroxyethyl) disulfide; the thermal stability of the tannic acid-based polyurethane gradually increases with the increase of the amount of tannic acid, and the thermal stability of the tannic acid-based polyurethane gradually decreases with the increase of the amount of bis(2-hydroxyethyl) disulfide; when the self-healing temperature is 80°C and the time is 3h, the self-healing efficiency of STPU3 is 95%, and the self-healing efficiency is high; the tannic acid-based polyurethane STPU3 is enzymatically hydrolyzed with lipase, and after 140 hours, the weight loss of STPU3 is 68.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Figure 2 is a diagram of the synthesis steps of tannic acid-based polyurethane.

[0021] Figure 2 FTIR spectrum and Raman spectrum of tannic acid-based polyurethane.

[0022] Figure 3 This is the DSC diagram of tannic acid based polyurethane.

[0023] Figure 4 This is the thermogravimetric diagram of tannic acid-based polyurethane.

[0024] Figure 5 This is a diagram of the mechanical properties of tannic acid-based polyurethane.

[0025] Figure 6 The stress-strain curves of tannic acid-based polyurethane self-healing (a, b, c, d, e, f, g) and the self-healing efficiency after heating for 3 hours (h).

[0026] Figure 7 This is a graph showing the relationship between the weight loss rate of tannic acid-based polyurethane enzymatic degradation and time. DETAILED DESCRIPTION

[0027] Embodiment 1: A self-healing tannic acid-based polyurethane film, using tannic acid as a cross-linking agent, castor oil as a polyol of polyurethane, isophorone diisocyanate as a polyisocyanate of polyurethane, bis(2-hydroxyethyl) disulfide and 1,4-butanediol as chain extenders of polyurethane, and the tannic acid-based polyurethane is prepared based on a prepolymer method.

[0028] When preparing the tannic acid-based polyurethane, the solvents are butanone and N,N-dimethylformamide, the butanone and N,N-dimethylformamide are dehydrated using activated 4a type molecular sieves, and the dehydration time is one week; the castor oil is vacuum dried at 120° C. for 2 hours; the 1,4-butanediol and tannic acid are vacuum dried at 60° C. for 3 hours before use.

[0029] The above reagents are all commercially available products, specifically isophorone diisocyanate (IPDI), castor oil (CO), 1,4-butanediol (BDO), bis(2-hydroxyethyl) disulfide (HEDS), dibutyltin dilaurate (DBTDL), tannic acid (TA) and N,N-dimethylformamide (DMF), which were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and butanone was purchased from Huzhou Shuanglin Chemical Technology Co., Ltd.

[0030] Embodiment 2: A method for preparing a self-healing tannic acid-based polyurethane, comprising the following steps:

[0031] Accurately weighed castor oil (CO) and bis(2-hydroxyethyl) disulfide (HEDS) are added to a round-bottom flask under a nitrogen atmosphere, and the mixture is heated to 70°C under constant stirring, and isophorone diisocyanate (IPDI) is slowly added, and then 10 μl of dibutyltin dilaurate (DBTDL) is added as a catalyst, and 10 ml of butanone is added, and the reaction is continued for 2 hours to obtain a prepolymer; thereafter, a certain amount of tannic acid (TA) dissolved in N, N-dimethylformamide (DMF) is added while keeping the heating temperature unchanged, and further reacted with 1, 4-butanediol (BDO) for about 4 hours to obtain a tannic acid-based polyurethane. The synthesis steps are as follows: Figure 1 shown.

[0032] Example 3: Application of a self-healing tannic acid-based polyurethane for preparing a tannic acid-based polyurethane film.

[0033] The preparation method of the tannic acid-based polyurethane film is as follows: prepare an appropriate amount of tannic acid-based polyurethane, transfer it to a dry and clean polytetrafluoroethylene film mold (with a specification size of 80 mm×80 mm×10 mm), and perform a curing treatment for 48 hours at room temperature; then transfer it to a 60° C. forced air oven and dry it for 48 hours. Carefully remove the film and store it in a desiccator for later use.

[0034] The following specific experiments are used for testing and characterization:

[0035] 1. Basic testing and characterization:

[0036] (1) Use infrared spectrometer (FT-IR) and Raman spectrometer to characterize the film;

[0037] FTIR spectrum and Raman spectrum of tannic acid based polyurethane are shown in the figure below: Figure 2As shown. Figure 2 From (a) to (c), it can be seen that the C=O stretching band of the polyurethane bond appears at 1710 cm -1 The NH stretching zone and bending zone appear at 3330cm -1 and 1525cm -1 In addition, 2260cm -1 The -NCO stretching band at the position disappears, indicating that the isocyanate groups have been completely consumed, which can indicate that the polyurethane is successfully prepared. Figure 2 (b) and Figure 2 It can also be seen in (c) that with the increase in the amount of crosslinking agent tannic acid, the -1 The stretching band of OH and 1710cm -1 The stretching band of C=O at the position gradually increases and red shifts, which indicates that tannic acid has been successfully introduced into the polyurethane chain. Figure 2 (d) It can be seen that 510cm -1 and 640cm -1 The peaks at correspond to the characteristic peaks v(SS) and v(CS), indicating that bis(2-hydroxyethyl) disulfide has been successfully introduced into the polyurethane backbone.

[0038] (3) Determine the glass transition temperature of the film by differential scanning calorimetry (DSC);

[0039] The glass transition temperature (Tg) of tannic acid-based polyurethane films is as follows: Figure 3 As shown. It is not difficult to see that with the increase of tannic acid dosage, the glass transition temperature (Tg) of tannic acid-based polyurethane gradually increases from 57.6℃ of PU to 58.5℃ of TPU3. However, with the increase of bis(2-hydroxyethyl) disulfide dosage, the glass transition temperature (Tg) of tannic acid-based polyurethane remains unchanged.

[0040] Analysis of the reasons for the increase in glass transition temperature Tg may be that on the one hand, the introduction of tannic acid as a rigid molecule increases the hardness of the polyurethane chain; on the other hand, the three-dimensional cross-linked network formed in the system limits the movement ability of the polyurethane molecular segments.

[0041] (4) Determine the heat resistance of the film using a thermogravimetric analyzer (TGA);

[0042] The thermogravimetric decomposition of self-healing polyurethane has three stages. The first stage is the decomposition of disulfide bonds, the second stage is the decomposition of hard segments, that is, the decomposition of urethane bonds, and the third stage is the decomposition of soft segments.

[0043] from Figure 4As can be seen in (a), as the amount of tannic acid increases, the thermal stability of tannic acid-based polyurethane gradually increases. This is mainly because the tannic acid in the tannic acid-based polyurethane has a multi-benzene ring structure and high thermal stability, thereby enhancing the heat resistance of the polyurethane system. In addition, the introduction of chemical cross-linking may also have a certain promoting effect on the improvement of the thermal stability of the film. The introduction of tannic acid has an improving effect on the heat resistance of the polyurethane film. Figure 4 As can be seen in (b), with the increase of the amount of bis(2-hydroxyethyl) disulfide, the thermal stability of tannic acid-based polyurethane gradually decreases. The reason for this phenomenon is that the bond energy of the disulfide bond is lower than that of the carbon-carbon bond and the carbon-hydrogen bond.

[0044] (5) Using a tensile strength testing machine to measure the mechanical properties of the membrane;

[0045] The mechanical properties of the samples were measured by a universal testing machine. Figure 5 As shown. Figure 5 (b) It can be seen that the tensile strength of the polyurethane film increases with the increase of the amount of tannic acid used. This is mainly because tannic acid, as a multifunctional cross-linking agent, can construct a three-dimensional cross-linking network in the system, and may also further produce hydrogen bonds with the polyurethane molecular chain segments to increase the intermolecular force. The elongation at break of the polyurethane film decreases with the increase of the amount of tannic acid used. This is mainly because the degree of entanglement between the polyurethane molecular chains increases and the introduction of tannic acid with a multi-benzene ring structure enhances the rigidity of the chain segments, limiting the mobility of the polyurethane molecular chains. The bond energy of the disulfide bond is lower than that of the carbon-carbon double bond and the carbon-hydrogen bond, which is about 60%, so the tensile strength and elongation at break of the polyurethane decrease with the increase of the amount of bis(2-hydroxyethyl) disulfide used.

[0046] 2. Self-repair performance test

[0047] The film was scratched with a blade to about 50% of the sample thickness, and the scratched film was allowed to self-heal at 80°C and different time periods, and then the mechanical properties of the film were measured using a tensile strength tester. The self-healing efficiency η was calculated using the following formula:

[0048]

[0049] Where oHealed is the average tensile strength of the repaired specimen, and σOrigin is the average tensile strength of the initial specimen.

[0050] The change of self-healing efficiency of tannic acid-based polyurethane over time is shown in Table 1.

[0051] Table 1 Changes of self-healing efficiency of tannic acid-based polyurethane over time

[0052]

[0053] It can be seen from Table 1 that when the self-healing temperature is 80°C and the time is 3h, the self-healing efficiency of PU is the lowest, which is only 51%; the self-healing efficiency of STPU3 is the highest, which is 95%. Figure 6 are the stress-strain curves of tannic acid-based polyurethane self-healing (a, b, c, d, e, f) and the self-healing efficiency after heating at 80 °C for 3 h (g). Figure 6 (a) Figure 6 (b) Figure 6 (c) Figure 6 (d) Figure 6 (e) and 6(f) correspond to PU, TPU1, TPU2, TPU3, STPU1, STPU2, and STPU3, respectively.

[0054] from Figure 6 It can be seen that the self-healing efficiency of tannic acid-based polyurethane increases with the increase of tannic acid dosage and increases with the increase of bis(2-hydroxyethyl) disulfide dosage.

[0055] Therefore, the mechanism of the self-healing process of polyurethane can be attributed to the following four aspects: (1) the high mobility of the polyurethane soft segment at higher temperatures is the prerequisite for the self-healing process, which provides an opportunity for the rearrangement of the molecular chains in the polyurethane matrix to repair the crack surface; (2) the dynamic cleavage of phenol-carbamate bonds and disulfide bonds at high temperatures; (3) the equilibrium of the reconnection of phenol-carbamate bonds and the exchange of hydrogen bonds at moderate temperatures; and (4) the dynamic exchange of disulfide bonds in the polyurethane chains.

[0056] 3. Degradation performance test

[0057] Prepare membrane samples (4cm×4cm) and perform enzymatic hydrolysis. Lipase (10mg / mL) was added to 0.1wt% MgCl2 (2mL) solution to study its degradation behavior; the sample was placed in a vial containing 10mL phosphate buffer solution (PBS, 100mM, pH=7.4) and then incubated at 52.5℃ with cyclic shaking. The weight loss rate was calculated as follows:

[0058]

[0059] Where m0 and m1 represent the weight of the membrane before and after degradation, respectively.

[0060] The biodegradability of polyurethane was verified by enzyme degradation method. Lipase was used to degrade the polyurethane film STPU3 because the self-healing rate of STPU3 film was the highest. The relationship between degradation weight loss and time is shown in Figure 2. Figure 7As shown. After 140h of enzymatic hydrolysis, the weight loss of membrane STPU3 was 68.3%. The triglyceride structure in castor oil and tannic acid does not participate in the polymerization of polyurethane and remains in the tannic acid-based polyurethane. Lipase belongs to carboxylic acid ester hydrolase, which gradually hydrolyzes the triglyceride structure.

[0061] In summary, the present invention uses tannic acid as a crosslinking agent, castor oil as a polyol of polyurethane, isophorone diisocyanate as a polyisocyanate of polyurethane, bis(2-hydroxyethyl) disulfide and 1,4-butanediol as chain extenders of polyurethane, and prepares a tannic acid-based polyurethane based on a prepolymer method. The glass transition temperature (Tg) of the tannic acid-based polyurethane film gradually increases with the increase of the amount of tannic acid, while the glass transition temperature (Tg) of the tannic acid-based polyurethane remains unchanged with the increase of the amount of bis(2-hydroxyethyl) disulfide; the thermal stability of the tannic acid-based polyurethane gradually increases with the increase of the amount of tannic acid, and the thermal stability of the tannic acid-based polyurethane gradually decreases with the increase of the amount of bis(2-hydroxyethyl) disulfide; when the self-healing temperature is 80°C and the time is 3h, the self-healing efficiency of STPU3 is 95%; the tannic acid-based polyurethane STPU3 is enzymatically hydrolyzed with lipase, and after 140 hours, STPU3 loses 68.3% of its weight.

Claims

1. A self-healing tannic acid-based polyurethane, characterized in that: The tannic acid-based polyurethane is prepared based on a prepolymer method by using tannic acid as a crosslinking agent, castor oil as a polyol of polyurethane, isophorone diisocyanate as a polyisocyanate of polyurethane, bis(2-hydroxyethyl) disulfide and 1,4-butanediol as chain extenders of polyurethane.

2. A self-healing tannic acid-based polyurethane according to claim 1, characterized in that: When preparing the tannic acid-based polyurethane, the solvents are butanone and N,N-dimethylformamide, and the butanone and N,N-dimethylformamide are dehydrated using activated 4a type molecular sieves for a dehydration time of one week.

3. A self-healing tannic acid-based polyurethane according to claim 1, characterized in that: The castor oil was vacuum dried at 120° C. for 2 h; and the 1,4-butanediol and tannic acid were vacuum dried at 60° C. for 3 h before use.

4. A method for preparing a self-healing tannic acid-based polyurethane according to any one of claims 1 to 3, characterized in that: The following steps are involved: Accurately weighed castor oil and bis(2-hydroxyethyl) disulfide are added to a round-bottom flask under a nitrogen atmosphere, the mixture is heated under constant stirring, isophorone diisocyanate is slowly added, and then a catalyst and butanone are added to react to obtain a prepolymer; keeping the heating temperature unchanged, tannic acid and 1,4-butanediol dissolved in N,N-dimethylformamide are added to further react to obtain a tannic acid-based polyurethane.

5. A self-healing tannic acid-based polyurethane according to claim 4, characterized in that: The heating temperature is 70°C.

6. A self-healing tannic acid-based polyurethane according to claim 4, characterized in that: The catalyst is dibutyltin dilaurate.

7. The use of a self-healing tannic acid-based polyurethane according to any one of claims 1 to 3, characterized in that: Used to prepare tannic acid-based polyurethane films.

8. The use of a self-healing tannic acid-based polyurethane according to claim 7, characterized in that: The preparation method of the tannic acid-based polyurethane film is as follows: the prepared tannic acid-based polyurethane is transferred to a dry and clean polytetrafluoroethylene film mold, and cured at room temperature; then the film is transferred to a blast oven for drying, and the tannic acid-based polyurethane film is carefully removed to obtain the film.

9. The use of a self-healing tannic acid-based polyurethane according to claim 8, characterized in that: The curing time is 48h.

10. The use of a self-healing tannic acid-based polyurethane according to claim 8, characterized in that: The temperature in the blast oven is 60° C., and the drying time is 48 hours.

Citation Information

Cited By

  • Special coated high-tower compound fertilizer for herbal flowers and preparation method of special coated high-tower compound fertilizer

    CN122010639A